Communications Act 2021 - William Lehr; Douglas Sicker (International Telecommunications Society (ITS), 2017)
The Communications Act of 1934, as amended by the Telecommunications Act of 1996, is showing its age.1 Like an old New England house that added drafty new additions over the years to accommodate a growing extended family, the Act is poorly suited to meet today's challenges. Much of what is included in the Act relates to earlier technologies, market structures, and regulatory constructs that address issues that are either no longer relevant or that cause confusion when one tries to map them to current circumstances. The legacy Act was crafted in a world of circuit-switched POTS2 telephony provided by public utilities, and even when substantially revised in 1996, barely mentions broadband or the Internet.3 Moreover, the FCC has struggled in recent years to establish its authority to regulate broadband services and in its effort to craft a framework to protect an Open Internet (sometimes, referred to as Network Neutrality). While many of the fundamental concerns that the legacy Act addressed remain core concerns for public policy, the technology, market, and policy environment are substantially changed. For example, we believe that universal access to broadband and Internet services is an important policy goal, but do not believe that the current framework enshrined in Title II of the legacy Act does a good job of advancing those goals. Additionally, spectrum policy within the FCC is too closely mired in legacy decisions that blend management of scarce spectrum resources with media content considerations4 and industrial policy. In this paper, we identify the key concerns that a new Act should address and those issues in the legacy Act that may be of diminished importance. We propose a list of the key Titles that a new Communications Act of 2021 might include and identify their critical provisions. Our straw man proposal includes six titles: Title I establishes the basic goals of the Act and sets forth the scope and authority for the FCC; Title II provides the basic framework for regulating potential bottlenecks; Title III establishes a framework for monitoring the performance of communications markets, for addressing market failures, and for promoting industrial policy goals; Title IV focuses on managing radio-frequency spectrum; Title V focuses on public safety and critical infrastructure; and Title VI addresses the transition plan. Our goal is to provoke a discussion about what a new Act might look like in an ideal, clean-slate world; not to address the political, procedural, or legal challenges that necessarily would confront any attempt at major reform. That such challenges are daunting we take as given and as a partial explanation for why the legacy Act has survived so long. Nevertheless, it is worthwhile having a clear picture of what a new Communications Act should include and the benefits that having a new Act might offer so we can better judge what our priorities ought to be and what reforms might best be attempted.
Keywords: 330